Análise cinemática da marcha em esteira por meio de ciclogramas em jovens e idosos de ambos os gêneros - Abreu, Ródney Silva (2013)
Cyclograms are gait analysis tools that characterizes the geometric aspect of the pattern of locomotion. These are angle-angle diagrams, very useful for representing cyclic patterns such as walking. The hypothesis of this study was that the parameters extracted from the hip-knee cyclograms could identify age and sex of volunteers during walking on a treadmill with 0˚ to 5˚ slopes. Subjects were 40 physically active healthy adult volunteers, 20 young people (10 males) and 20 elderly (10 males). The volunteers were divided into 4 groups (young male group (JM), young female group (JF), elderly male group (IM) and elderly female group (IF)) and the average of parameters area (A), perimeter (P) and the ratio P/√A of cyclogram were calculated, as the speed and cadence. The average speed of JM was higher than IM (p=0,00) and was higher than JF to IF (p=0,00), while no differences were found between JM and JF (p=0,59), nor between IM and IF (p=0,95). The parameters extracted directly from cyclogram allow to discriminate the studied groups according to age (p<0,05), especially with treadmill inclined a 5˚, but it was not enough to determine the gender (p>0,508). The results were partially confirmed, because there were differences by age, but not between males and females.